Effectiveness of Supportive Care Interventions on Psychological Distress in Breast Cancer Patients - Desi Lianti Sari Hasibuan; Dudut Tanjung; Farida Linda Sari Siregar (GLOBAL HEALTH SCIENCE GROUP, 2024)
Supportive care interventions (SCI) are interventions used as symptom management of the side effects of breast cancer disease and treatment. This study aims to analyze the effectiveness of supportive care interventions on psychological distress in patients diagnosed with breast cancer. The research method used a quasi-experimental non-equivalent design with control group pretest-posttest, the research sample was 50 respondents consisting of two groups with each group of 25 respondents. Psychological distress (PD) was assessed using the Hospital Anxiety and Depression Scale (HADS. The bivariate analysis used was paired t-test and independent t-test. The results showed that there was a significant difference in psychological distress in the intervention group and control group after supportive care interventions with an average value of psychological distress (anxiety) in the intervention group (Mean = 4.16; SD = 1.700) and the control group (Mean = 0.24; SD = 0.879), while the average value of psychological distress (depression) in the intervention group was (Mean = 3.24; SD = 1.53) and the control group (Mean = 0.28; SD = 0.76). Statistical results obtained p=0.001 (<0.05). The conclusion of this study is that there is an effectiveness of supportive care interventions on psychological distress of breast cancer patients.